Cloning of the wheat Yr15 resistance gene sheds light on the plant tandem kinase-pseudokinase family - Valentina Klymiuk (Nature Portfolio, 2018)
Yellow rust fungus severely limits global wheat production and breeding of durable resistance is challenging. Here Klymiuk et al. isolate the broad-spectrum Yr15 resistance gene from wild emmer wheat and show that it is a member of a distinct tandem kinase-pseudokinase family of plant proteins.